2018
DOI: 10.1136/bmjspcare-2017-001457
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, tolerability and acceptability of oxycodone for cancer-related pain in adults: an updated Cochrane systematic review

Abstract: Oxycodone offers similar levels of pain relief and adverse events to other strong opioids. However, hallucinations occurred less with CR oxycodone than with CR morphine, but the quality of this evidence was very low, so this finding should be treated with utmost caution. Our conclusions are consistent with other reviews and suggest that oxycodone can be used first line as an alternative to morphine. However, because it is cheaper, morphine generally remains the first-line opioid of choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…The incidence of nausea was 20% to 27%, while the incidence of vomiting was 11.5% to 15%. 30,31 Recently, several studies have evaluated the effect of IV oxycodone on postoperative analgesia. Zhang et al 16 investigated the effect of oxycodone in patients undergoing open hepatectomy and reported that the incidence of PONV was approximately 35% when dexmedetomidine was combined perioperatively and 55% without dexmedetomidine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of nausea was 20% to 27%, while the incidence of vomiting was 11.5% to 15%. 30,31 Recently, several studies have evaluated the effect of IV oxycodone on postoperative analgesia. Zhang et al 16 investigated the effect of oxycodone in patients undergoing open hepatectomy and reported that the incidence of PONV was approximately 35% when dexmedetomidine was combined perioperatively and 55% without dexmedetomidine.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the incidence of nausea and vomiting with oral oxycodone for cancer‐related pain control. The incidence of nausea was 20% to 27%, while the incidence of vomiting was 11.5% to 15% . Recently, several studies have evaluated the effect of IV oxycodone on postoperative analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…Recent Cochrane reviews found overall evidence that oxycodone provided similar analgesic and adverse effects to morphine, concluding that these agents could be interchangeable in the frontline treatment setting for cancer-related pain. 89,90 Studies of oxycodone/naloxone formulations showed effective analgesia with reduced opioid-induced constipation for long-term use in cancer-related pain. 91,92 Oxymorphone is an opioid agonist that acts primarily at the mu-opioid receptor.…”
Section: Codeinementioning
confidence: 99%
“…However, experiments have suggested that the antinociceptive effect of oxycodone can be inhabited by selective µ-opioid receptor antagonists, such as β-funaltrexamine (β-FNA), but not by selective κ-opioid receptor antagonists [29,30]. Oxycodone has intravenous, subcutaneous, intramuscular, and oral formulations, and oral formulations includes immediate-release (IR) tablets (for 4-hourly dosing) and sustained (controlled-release (CR)) release tablets (for 12-hourly dosing) [31].…”
Section: Role Of Oxycodone Hydrochloride Prolonged-release Tablets Inmentioning
confidence: 99%